The transmission and diagnosis of 2019 novel coronavirus infection disease (COVID‐19): A Chinese perspective - Han, Yu; Yang, Hailan (Journal of medical virology, 2020)
2019 novel coronavirus (SARS‐CoV‐2), which originated in Wuhan, China, has attracted the world's attention over the last month. The Chinese government has taken emergency measures to control the outbreak and has undertaken initial steps in the diagnosis and treatment of 2019 novel coronavirus infection disease (COVID‐19). However, SARS‐CoV‐2 possesses powerful pathogenicity as well as transmissibility and still holds many mysteries that are yet to be solved, such as whether the virus can be transmitted by asymptomatic patients or by mothers to their infants. Our research presents selected available cases of COVID‐19 in China to better understand the transmission and diagnosis regarding this infectious disease. Research Highlights The research includes important information regarding the transmission and diagnosis of COVID‐19. The clinical report could be very useful for clinicians. SARS‐CoV‐2 possesses powerful pathogenicity and transmissibility. Patients with negative swabs may also be diagnosed with COVID‐19.